Disease specific symptoms indices in patients with celiac disease—A hardly recognised entity - Jabeen, Shaista; Khan, Azmat Ullah; Ahmed, Waqas; Ahmad, Mansur-ud-Din; Jafri, Saghir Ahmad; Bacha, Umar; Ali, Amjed; Muzammil, Hafiz Shehzad; Alsagaby, Suliman A.; Al Abdulmonem, Waleed; Abdelgawad, Mohamed A.; Riaz, Mishal; et al. (Frontiers in Nutrition, 2022)
Background Celiac disease (CD) was considered a rare disease before and was perceivably only limited to children but now affects almost 1–2% of the global population. This abrupt increase in prevalence is due to advancements in diagnostic criteria and medical facilities but still many countries lack the basic data that can assess the severity of this health issue. The present study was conducted with the aim to assess the common but rarely diagnosed condition with the identification of its underlying secondary ailments. Materials and methods Patients visiting public sector hospitals were recruited and tested for clinical symptoms secondary to gluten-containing foods (wheat and barley, etc.), followed by serological testing for immunoglobulin A, tissue transglutaminase A, and anti-endomysial antibodies. Only seropositive candidates were included in the endoscopic and biopsy examination for the features of villous atrophy and intestinal cell damage. The secondary ailments including anemia, growth retardation, and gastrointestinal symptoms were also documented for the tested positive patients. The modified European Society of Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) criterion was followed throughout the study. Results From 647 suspected cases from March 2018 to July 2019, 113 were confirmed with CD while 58% were female children and 42% were male children. The majority of them were from a lower class (75%) and 26% of them had a positive family history of CD. A total of 67% of patients with CD were underweight while wasting was observed in 38%, and 80% were stunted as well. Of the positively tested patients with CD, 49% had moderate anemia with 15% having severe anemia. Approximately 33% had hypoalbuminemia as well. The majority of them had a mild to severe range of gastrointestinal symptoms, such as abdominal pain, diarrhea, flatus, eructation, diarrhea, and steatorrhea. Conclusion The study finding indicates an increased number of patients diagnosed with CD with an excessive sum of secondary ailments, such as anemia, growth failure, growth retardation, malnutrition, and gastrointestinal symptoms.